Better use of primary care laboratory services following interventions to 'market' clinical guidelines in New Zealand: a controlled before-and-after study. Issue 3 (12th January 2011) - Tomlin, Andrew; Dovey, Susan; Gauld, Robin; Tilyard, Murray
Abstract : Context: Laboratory tests for inflammatory response, thyroid function and infectious diarrhoea were not being ordered as recommended by clinical guidelines. Objective: To measure changes in community laboratory-test ordering following marketing programmes promoting guidelines recommendations. Design: Controlled before-and-after study involving 2 years of national laboratory payment data before and after each intervention. Comparisons were with doctors ordering the same tests but not receiving interventions. Setting: New Zealand primary care. Participants: 3161, 3140 and 3335 general practitioners and 2424, 2443 and 2766 Comparison doctors ordering inflammatory response, thyroid function and acute diarrhoea tests from community laboratories, July 2003 to March 2009. Interventions: Three separate marketing programmes to general practitioners, each comprising written material advising of guidelines recommendations, individual laboratory-test use feedback and professional development opportunities. Main outcome measures: Number of tests, tests/doctor, patients having tests and tested patients/doctor/year before and after each intervention. Change in expenditure from before each intervention to after. Results: For Intervention doctors, erythrocyte sedimentation rate tests decreased 60.0% after the intervention; tests for C-reactive protein increased 63.1%; simultaneous erythrocyte sedimentation rate and C-reactive protein orders decreased 32.6%. Tests for free thyroxine and free triiodothyronine decreased 44.1% and 36.0%. The proportion of thyroid function tests where thyroid-stimulating hormone was the sole test ordered increased from 43.2% before the intervention to 65.2% afterwards (p<0.001; 95% CI 21.7% to 22.2%). Testing for faecal culture decreased 31.5%, giardia and cryptosporidium 31.5%, and ova and parasites 56.9%. Faecal culture as the sole initial test increased from 31.4% to 39.1% (p<0.001; 95% CI 7.2% to 8.2%). Testing by Comparison doctors changed in the same direction but with significantly less magnitude. The estimated reduction in expenditure for study tests was 23.5%. Conclusions: Clear information marketed to general practitioners improved the quality of laboratory test ordering for patients in New Zealand.